The Comparative Effectiveness of Phaleria macrocarpa (Scheff.) Boerl. Pericarp Ethanol Extract and Metformin in Reducing Blood Sugar Levels and Ameliorating the Langerhans Islets Degeneration in Diabetic Rat Models - Eman Sutrisna; Qurrotu Aini; Ika Murti Harini; Nur Signa Aini Gumilas; Mustofa Mustofa; Evy Sulistyoningrum (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2020)
Phaleria macrocarpa (Scheff.) Boerl. has been widely used in the treatment of diabetes mellitus but its effectiveness is still inconclusive so it needs to be compared with standard drugs such as metformin. This study aims to analyze the effects of P. macrocarpa fruit extracts on blood sugar levels and the repairing of the pancreatic Langerhans islets of diabetic rat models. The study was conducted experimentally by pre and post-test design with a control group. Thirty white rats were divided into 6 groups. All rats were treated with 40 mg/200 g BW of streptozotocin (STZ) to induce hyperglycemia, except group I. Group II as a negative control was given with aquadest. Group III, IV, and V were given with ethanol extract of P. macrocarpa pericarps at doses of 200, 250, and 300 mg/200 g BW/day, respectively. Group VI was given with metformin at a dose of 150 mg/200 g BW/day. On the 22nd day of treatment, blood specimens were taken for examination of fasting blood sugar levels and pancreatic organs were analyzed for histopathological examination of the islets of pancreatic Langerhans. The data were statistically analyzed with α<0.05; CI95%. Paired sample t-test results showed a significant decrease in blood sugar levels before and after treatment in group V (p-value=0.048). One way anova and post hoc Least Significant Difference (LSD) test results showed a significant difference in mean blood sugar levels after the final treatment between groups I and II (p-value=0.013), I and III (p-value=0.004), I and IV (p-value=0.002), I and VI (p-value=0.000), II and VI (p-value=0.031), and V with VI (p-value=0.005); one way anova and post hoc LSD test results showed a significant difference in the mean area of islets of pancreatic Langerhans between group I and all treatment groups (p-value=0.000), II with V and VI (p-value=0.000 and 0.009), III with V and VI (p-value=0.000 and 0.001), and IV with V (p-value=0.003). It can be concluded that the extract of P. macrocarpa pericarps showed a hypoglycemic effect and repaired the damage in Langerhans islets of STZ-induced rat in a dose-dependent manner.